Peran Penting Putusan MK Nomor 60/PUU-XXII/2024 dan Putusan MK Nomor 70/PUU-XXII/2024 dalam Keberlangsungan Demokrasi Indonesia (Deposisi: Jurnal Publikasi Ilmu Hukum, 2025)
History often repeats itself in different contexts, as seen in the political dynamics of Indonesia in 2024, which are similar to the events of 1998. Although it has not yet reached the escalation of reforms, political tensions, polarization of society, and dissatisfaction with the government are the main issues. The fall in the Democracy Index reflects a weakening of freedom of opinion, human rights, and political participation. The wave of massive demonstrations against the revision of the 2024 Pilkada law showed resistance from various elements of society, including students, workers, artists, and public figures. Demonstrators demanded that the DPR comply with Constitutional Court decision Number 60/PUU-XXII/2024 regarding the threshold for the nomination of regional heads and Constitutional Court decision Number 70/PUU-XXII / 2024 regarding the age limit for candidates for regional heads. This research is a literature study with qualitative methods and a normative legal approach, including statutory, case, and conceptual analysis. The Data was obtained through the analysis of relevant legal and regulatory documents, as well as public opinion published in online media. This study provides an overview of the current challenges of Indonesian democracy as well as the implications of legal decisions on national political dynamics.